Tachysterol2 increases the synthesis of fibroblast growth factor 23 in bone cells - Ewendt, Franz; Kotwan, Julia; Ploch, Stefan; Feger, Martina; Hirche, Frank; Föller, Michael; Stangl, Gabriele I. (Frontiers in Nutrition, 2022)
Tachysterol2 (T2) is a photoisomer of the previtamin D2 found in UV-B-irradiated foods such as mushrooms or baker’s yeast. Due to its structural similarity to vitamin D, we hypothesized that T2 can affect vitamin D metabolism and in turn, fibroblast growth factor 23 (FGF23), a bone-derived phosphaturic hormone that is transcriptionally regulated by the vitamin D receptor (VDR). Initially, a mouse study was conducted to investigate the bioavailability of T2 and its impact on vitamin D metabolism and Fgf23 expression. UMR106 and IDG-SW3 bone cell lines were used to elucidate the effect of T2 on FGF23 synthesis and the corresponding mechanisms. LC-MS/MS analysis found high concentrations of T2 in tissues and plasma of mice fed 4 vs. 0 mg/kg T2 for 2 weeks, accompanied by a significant decrease in plasma 1,25(OH)2D and increased renal Cyp24a1 mRNA abundance. The Fgf23 mRNA abundance in bones of mice fed T2 was moderately higher than that in control mice. The expression of Fgf23 strongly increased in UMR106 cells treated with T2. After Vdr silencing, the T2 effect on Fgf23 diminished. This effect is presumably mediated by single-hydroxylated T2-derivatives, since siRNA-mediated silencing of Cyp27a1, but not Cyp27b1, resulted in a marked reduction in T2-induced Fgf23 gene expression. To conclude, T2 is a potent regulator of Fgf23 synthesis in bone and activates Vdr. This effect depends, at least in part, on the action of Cyp27a1. The potential of oral T2 to modulate vitamin D metabolism and FGF23 synthesis raises questions about the safety of UV-B-treated foods.